2015
DOI: 10.1371/journal.pone.0118184
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Screening for Anti-Osteoporotic Fraction from Extract of Herbal Formula Xianlinggubao in Ovariectomized Mice

Abstract: Background and ObjectivesTraditional Chinese Medicine (TCM) Fufang or formula Xianlinggubao (XLGB) is a prescribed TCM drug in China registered for prevention and treatment of osteoporosis. Fufang in TCM is comprised of a group of herbal compounds contributing in group to the treatment efficacy. The present study aims to identify the bioactive fraction(s) in XLGB extract that account(s) dominantly for its osteogenic effects.MethodsThe extract of XLGB formula was separated into three fractions using chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…XLGB capsule is an extensively used remedy in Chinese natural medicine for the treatment of osteoporosis [101]. It has been reported that XLGB shows anti-osteoporosis activity in ovariectomized mice [102,103] and rats with oral dosages at 236 mg/kg/day and 270 mg/kg/day, respectively [47]. Moreover, the dose up to 1800 mg/kg/day showed no serious side effects in ovariectomized rats.…”
Section: Antiosteoporosis Effectmentioning
confidence: 99%
“…XLGB capsule is an extensively used remedy in Chinese natural medicine for the treatment of osteoporosis [101]. It has been reported that XLGB shows anti-osteoporosis activity in ovariectomized mice [102,103] and rats with oral dosages at 236 mg/kg/day and 270 mg/kg/day, respectively [47]. Moreover, the dose up to 1800 mg/kg/day showed no serious side effects in ovariectomized rats.…”
Section: Antiosteoporosis Effectmentioning
confidence: 99%
“…For example, the herbal extract is a component in more than 30 herbal prescriptions for the treatment of osteoporosis where clinical trials have been reported . A recent study using an herbal formulae containing S. miltiorrhiza showed antiresorptive efficacy in OVX mice and rats . Our discovery that some of these compounds are effective ectosteric inhibitors of CatK helps to understand the molecular mechanism of action of the herbal anti‐osteoporotic efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…Postmenopausal osteoporosis originated from the cessation of ovarian hormones at menopause which prolongs bone loss. Phytoestrogen and essential amino acids are proven to modulate the growth and the differentiation of osteoblasts and possessing anti-osteoporotic effects (33,34). Therefore, the main goal of this study is to find natural treatment gathered these two properties.…”
Section: Discussionmentioning
confidence: 99%